Analysis of operations of port using mathematical and simulation modelling. Issue 3 (1st January 2015) - Rajendran, Suchithra; Srinivas, Sharan; Saha, Chanchal
This paper proposes an integer linear programming (ILP) and discrete event simulation (DES) models for minimising the waiting time of ships at Port of X (PoX). The port consists of three docks that accommodate different types of ships. Each dock is facilitated with a fixed number of berths that allow ships to be anchored, and there is a common access channel through which a ship enters or leaves the docks. The objective of this paper is to minimise the waiting time of ships while entering and leaving the port. First, an ILP model is developed to schedule the ships at the port and the effect of ship waiting time is observed. Due to the computational complexity of the ILP model, a DES model is developed. The experimental results indicate that capacity relocation of berths reduced the waiting time of ships by 77% compared to the current scenario.